Perbandingan Kinerja Server Virtual Pada Proses High Availability - Chairul Mukmin (Institute of Information Technology and Social Science (IITSS), 2020)
This research is motivated by the complexity of each company being required to provide services without limits and can be accessed at any time, this must be supported by a reliable system to support so that the services provided can be accessed at any time. For this reason, it is necessary to analyze the virtual machine specifically for server repair when it is decided on the service that is running. This research discusses about improving server performance on virtual machines by using vmware and proxmox as virtual machines. This research uses the action research method. Testing is done by measuring the use of server resources when using virtual machines from the main server to the backup server. The results showed that VMware was more efficient in using server resources with high availability of 22.9% CPU, 1.73 GB of memory and 4.07 MB network while Proxmox had greater use of existing resources with high availability of CPU 28.8%, memory 2, 15GB and a 2.03MB network. From the data above shows that VMware has a more stable performance compared to Proxmox in terms of resource server usage when the process is high.